Paclitaxel sensitizes gastric cancer cells to TRAIL-induced apoptosis - Lin Li; Jiafu Ji; Xianzi Wen; Biao Fan (临床与病理杂志; 卷 35, 编号 1 (6 2015), 2026)
Objective: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) holds promise for cancer therapy as it has unique capacity to selectively trigger apoptosis in cancer cells. We reported here that paclitaxel sensitized gastric cancer cells to TRAIL-induced apoptosis. Methods: After drug exposure, apoptosis rate and caspase activation were examined. Various proteins were detected by western blot. Several interventions, including pharmacological inhibitors and siRNA transfection were used. The growth inhibition of tumors was evaluated in SGC- 7901-implanted nude mice model. Results: We found gastric cancer cellsshowed a mixed response to TRAIL. Combined treatment with paclitaxel markedly enhanced TRAIL-induced apoptosis in vitro and in vivo. The underlying mechanisms involved in synergistical activation of caspase proteins, upregulation of receptors, down-regulation of antiapoptotic proteins and inactivation of MAPKs. Conclusion: TRAILinduced cytotoxicity and apoptosis can be synergistically enhanced by paclitaxel, suggesting the therapeutic potential of combining TRAIL plus paclitaxel in gastric cancer treatment.